The Epistles of John: Their Message and Relevance for Today - Ngewa, Samuel M. (Cascade Books, 2019)
While the message of the Bible remains the same, different insights may add new light. In this commentary attempt is made to interact with the text of the letters of John, especially as we have it in the Greek New Testament. The meaning of the word is not seen as the end but only as the basis upon which to relate the message to the present needs of the church. The church is both guardian of truth and instrument of love. These two themes are repeatedly found in the epistles of John, and as they are discussed in this commentary the writer seeks to provoke the reader to reflect on how he/she can keep on improving in them. In our times, with so many displaced persons, hospitality is increasingly becoming an aspect of Christian love the church cannot run away from. These are matters that this book calls attention to, as they are raised by the biblical text itself. I am grateful to others who have also given their time and energy in providing their insights on the same epistles. May the Lord use all the efforts to build a strong church for our time and many years to come!